The theory of the growth of the firm - Penrose, Edith Tilton (Oxford ; New York : Oxford University Press, 2009)
Edith Penrose's tightly argued classic laid the foundations for the resource based view of the firm, now the dominant framework in business strategy She analyses managerial activities and decisions, organizational routines, and also the factors that inevitably limit a firm's growth prospects. --from publisher's description.
The firm in theory -- The productive opportunity of the firm and the "entrepreneur" -- Expansion without merger : the receding managerial limit -- "Inherited" resources and the direction of expansion -- The economics of size and the economies of growth -- The economics of diversification -- Expansion through acquisition and merger -- The rate of growth of a firm through time -- The position of large and small firms in a growing economy -- Growing firms in a growing economy : the process of industrial concentration and the pattern of dominance.
Previous ed.: 1995.
Includes bibliographical references and index.
Keywords: Industries -- Size; Unternehmenswachstum